2018
DOI: 10.1016/j.stemcr.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cell Model of Nakajo-Nishimura Syndrome Untangles Proinflammatory Pathways Mediated by Oxidative Stress

Abstract: SummaryNakajo-Nishimura syndrome (NNS) is an immunoproteasome-associated autoinflammatory disorder caused by a mutation of the PSMB8 gene. Although dysfunction of the immunoproteasome causes various cellular stresses attributed to the overproduction of inflammatory cytokines and chemokines in NNS, the underlying mechanisms of the autoinflammation are still largely unknown. To investigate and understand the mechanisms and signal pathways in NNS, we established a panel of isogenic pluripotent stem cell (PSC) lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 65%
“…Induced pluripotent stem cells (iPSCs) were established from the fibroblasts of NNS#1 [14]. MLs were established from iPSCs bearing mutant homozygous PSMB8 (MT-iPS-MLs), their isogenic wild-type counterpart (WT-iPS-MLs), and from KhES1 ESCs bearing the same PSMB8 mutation (MT-ES-MLs) [14].…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Honda-Ozaki and Kanazawa reported the pluripotent stem cell model of NNS untangles proinflammatory pathways mediated by oxidative stress and found a specific ROS-mediated inflammatory pathway, providing a platform for the discovery of alternative therapeutic options for NNS and related immunoproteasome disorders [10] . Individual case studies using iPS cells will develop new effective treatments.…”
Section: Discussionmentioning
confidence: 99%